2017
DOI: 10.1016/j.aca.2017.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multivariate curve resolution strategies in quantitative LCxLC: Application to the quantification of furanocoumarins in apiaceous vegetables

Abstract: Comprehensive two-dimensional liquid chromatography (LC × LC) has been gaining popularity for the analysis of complex samples in a wide range of fields including metabolomics, environmental analysis, and food analysis. While LC × LC can provide greater chromatographic resolution than one-dimensional LC (1D-LC), overlapping peaks are often still present in separations of complex samples, a problem that can be alleviated by chemometric curve resolution techniques such as multivariate curve resolution-alternating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Other approaches, such as deconvolution or decomposition of the data, may also be applied to improve resolution beyond what is possible given the instrumental constraints. Examples include techniques such as Fourier self-deconvolution [86], wavelets [87], and multivariate curve resolution (MCR) [3]. In many cases, these deconvolution strategies can also be applied for background correction, as they allow one to separate peaks, background, and noise vectors.…”
Section: Signal Deconvolution and Resolution Enhancementmentioning
confidence: 99%
See 3 more Smart Citations
“…Other approaches, such as deconvolution or decomposition of the data, may also be applied to improve resolution beyond what is possible given the instrumental constraints. Examples include techniques such as Fourier self-deconvolution [86], wavelets [87], and multivariate curve resolution (MCR) [3]. In many cases, these deconvolution strategies can also be applied for background correction, as they allow one to separate peaks, background, and noise vectors.…”
Section: Signal Deconvolution and Resolution Enhancementmentioning
confidence: 99%
“…Apart from being a useful preprocessing tool, MCR can also be used to obtain information from chromatograms. Cook et al showed that it is quite useful for quantitation [3,141]. MCR resolves the components of a mixture by deconvoluting the data into response profiles and peak areas.…”
Section: Multivariate Curve Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a paper by Cook et al . discussed different strategies based on MCR‐ALS to carry out the quantification of several analytes (furanocoumarins in apiaceous vegetables) in multidimensional data.…”
Section: Peak Detection and Profilingmentioning
confidence: 99%